2012
DOI: 10.1371/journal.pone.0052941
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Microglial Activation in Amyotrophic Lateral Sclerosis

Abstract: There is growing evidence of activated microglia and inflammatory processes in the cerebral cortex in amyotrophic lateral sclerosis (ALS). Activated microglia is characterized by increased expression of the 18 kDa translocator protein (TSPO) in the brain and may be a useful biomarker of inflammation. In this study, we evaluated neuroinflammation in ALS patients using a radioligand of TSPO, 18F-DPA-714. Ten patients with probable or definite ALS (all right-handed, without dementia, and untreated by riluzole or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
167
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(177 citation statements)
references
References 34 publications
9
167
0
Order By: Relevance
“…PET with radioligand-binding biomarkers of activated microglia revealed that areas with the highest microglial activation in patients with ALS were the motor cortices, 39 thus corresponding to the distribution of signal changes and atrophy that we have detected in our group of patients.…”
mentioning
confidence: 52%
“…PET with radioligand-binding biomarkers of activated microglia revealed that areas with the highest microglial activation in patients with ALS were the motor cortices, 39 thus corresponding to the distribution of signal changes and atrophy that we have detected in our group of patients.…”
mentioning
confidence: 52%
“…In patients with ALS, microgliosis occurs specifically with motor neuron injury in the motor cortex, along the corticospinal tract, and in the ventral horn of the spinal cord [24,53,[69][70][71][72] radioligands that bind microglia, has been used to image microglial activation corresponding with the location motor neuron injury in patients with ALS [72,73]. This radiographic evidence in humans correlates the with evidence in the G93A mSOD1 transgenic mouse, which demonstrates microglial activation even before motor neuron cell death [74,75].…”
Section: Microgliamentioning
confidence: 97%
“…Uptake of TSPO ligands in the brain is generally low in normal healthy adults, but overall uptake is increased with age (146). An increase in TSPO expression has been observed during the onset of disease in amytrophic lateral sclerosis (ALS) patients (147). Similarly, brains of subjects with mild cognitive impairment (MCI), who are at an increased risk of developing Alzheimer's disease (AD), or subjects with mild and early forms of AD, exhibit higher ligand binding compared to age-matched controls (148,149) although other studies contradict this observation (150).…”
Section: Inflammatory Brain Conditionsmentioning
confidence: 99%